The Role of Artificial Intelligence in Optimizing Students' Academic Writing - Maria Angela Christin Tefa; Shaumi Rani; Sitti Saum Sayidaturrahmah; Elizabeth Lobo; I Nyoman Sudana Degeng; Otto Fajarianto (STAI Miftahul Ula Nganjuk, 2025)
The inability of some students to optimally utilize Artificial Intelligence (AI) in academic writing is a major challenge, despite the significant potential of this technology to support writing skills. This study aims to identify the role of Artificial Intelligence in optimizing students' academic writing in terms of systematic literature review, especially at the higher education level. The research method used Systematic Literature Review with PRISMA approach using Google Scholar database to screen relevant articles. The reviewed articles show that AIs such as ChatGPT, QuillBot, and Perplexity AI can improve the efficiency, structure, and technical quality of academic writing. The expected outcome of this research is a deeper understanding of how AI can be effectively integrated, while maintaining students' critical thinking skills, creativity, and academic integrity. It is important to ensure the use of AI is complemented by proper guidance so that the benefits of this technology can be maximized without compromising originality and in-depth analysis.